An Estimator for Torque and Draft Force Requirements of a New Up-cut Rotary Tiller - I Ahmadi (Ferdowsi University of Mashhad, 2020)
The aim of this study is to design, fabricate and evaluate a new type of up-cut rotary tiller and to develop correct formulas to estimate its torque and draft force using the laws of classical mechanics. In order to verify the model, a real-sized prototype of the rotary tiller was tested. It was hypothesized that four processes are involved to create the rotary tiller torque, namely soil cutting, soil lifting, soil-metal friction, and soil velocity. Furthermore, it was assumed that the horizontal components of soil cutting and soil-metal friction forces create the required draft of the machine. Based on these hypothesizes, mathematical formulas were developed to calculate torque, and draft requirements of the machine. To facilitate performing necessary calculations, the developed formulas were entered in a worksheet of the MS Excel software. According to the results of this study, the average experimental draft and torque of the machine tilling a silty clay loam soil were 16.8 N and 12.8 Nm, respectively. Furthermore, the average theoretical draft and torque of the machine were 13 N and 11.8 Nm respectively. These promising results can be considered as the accuracy check of the formulas developed herein.